Aleitamento materno como um direito humano: a guerra entre o seio e a mamadeira - Pereira, Bruna Tereza (2019)
The objective of this study is to study breastfeeding in order to identify whether the discourse produced by the commercial promotion of industrialized milk interferes with the practice of breastfeeding and its consolidation as a human right. It is based on the understanding that the practice of breastfeeding contributes to the promotion and defense of human rights, especially the Human Right to Adequate Food and the Right to Health, by increasing access to the first food of the human being: breast milk; and that the heritage of the precocious weaning culture coupled with the culture of modern society, accustomed to treating food as something to be solved quickly, makes it increasingly easy to market breastfeeding substitutes through commercial promotion, with messages that enter the consumer and convey ideas, supposedly, of well-being, nutrition and child health. The research was based on theoretical references from the perspective of some authors who discuss the theme. Also, it is conditioned to the scientific method, characterizing itself as exploratory, qualitative and case study. The data collection was done through the technique of interviews, applied through the instrument called interview form, composed of semi-structured questions and through the technique of participant observation. For the treatment and analysis of the data appropriated the theoretical-methodological current of Discourse Analysis of French orientation that has as precursors: Michel Pêcheux, Paul Henry and Michel Plon, brought to Brazil by Eni Orlandi. It was therefore evident that breastfeeding is imbued with social, economic, political and cultural determinants that represent an ideology, materializing through different discourses that over the years have made breastfeeding a practice that can be regulated by society. These discourses include the discourse of the industrialized milks industry, especially Nestlé, which is considered to be the main industry promoting infant formulas, and today, through its strategies, it has become one of the most influential marketings on the market. Among these strategies is the historically established relationship with health professionals, especially pediatricians, who are also responsible for spreading the brand and are considered reliable and authorized to indicate weaning. However, in the same way that commercial marketing of industrialized milks influences and interferes with the practice of breastfeeding, we conclude that this instrument can be used to promote the practice of exclusive breastfeeding, influencing behavior change and adherence to breastfeeding through social marketing.